Passion for an activity and its role on affect: Does personality and the type of activity matter? - Mylonopoulos, Nikolaos; Theoharakis, Vasilis (Frontiers in Psychology, 2023)
While personality traits play a crucial role in a person’s general affect, passion for an activity has been shown to partially mediate this relationship, with harmonious passion generally related to positive affect and obsessive passion to negative affect. However, activities are not all the same with some characterized as having “positive” consequences while others as having “negative” consequences. This study examines how passions manifest for two popular activities: physical exercise, an activity with in general “positive” consequences, and social media, an activity with potentially both “positive” and “negative” consequences. We replicate and extend earlier studies which have relied on baskets of heterogenous self-reported activities without distinguishing between activities. We find that, when fully controlling for personality, obsessive passion for physical exercise is positively associated with positive affect while obsessive passion for social media is positively associated with negative affect. However, harmonious passion for either activity has no significant association with any affect. Further, we find that passions for physical exercise relate with conscientiousness while passions for social media with neuroticism.